Effect of Non-Surgical Periodontal Treatment in Altering Salivary Concentration of Osteoprotegerin among Controlled Diabetics with Chronic Periodontitis - Walid Ftis; Kholoud Ftis; Ahmed Kishlaf; Laila Hamad; Helal Nsser (Khalij-Libya Journal of Dental and Medical Research, 2025)
Forty patients were included in the present study; they were divided equally into four equal groups (10 each): Group I include healthy subjects, Group II includes adult periodontitis patients free from any systemic diseases, Group III includes diabetics and periodontal healthy status and Group IV includes diabetic patients with chronic periodontitis. Group II and IV patients were subjected to mechanical plaque control procedure including complete mouth scaling and root planning, in order to improve their periodontal status. No initial periodontal therapy was performed in both other groups (Group I and III). Clinical evaluation was done through use of the following parameters, pocket depth measurement, attachment level measurement and gingival, plaque indices. These evaluations were done at baseline, one and three months. All included patients were evaluated at the beginning of the study and at the subsequent scheduled visits for salivary level of OPG using ELISA system. Results showed that Groups II and IV had an improvement in the entire measured clinical parameters following the completion of periodontal therapy. The mean values of OPG level recorded at baseline among the all included groups, showed increased values following the periodontal therapy in Group II and IV; such increase in OPG level was statistically significant. A reverse relationship between clinical signs of periodontal disease and level of OPG in saliva was noted. At baseline, mean of GI, PI and PD in diabetic chronic periodontitis group showed statistically significantly higher value compared with that of chronic periodontitis group. Regarding the mean of CAL there was no statistically significant difference between the two groups. Finally, through all periods, no statistically significant difference between % changes in GI, PI, PD and CAL of the two groups was noted.